2014
DOI: 10.1016/j.electacta.2014.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Ti atoms in Ru0.3Ti0.7O2 mixed oxides form active and selective sites for electrochemical chlorine evolution

Abstract: The electrocatalytic properties of the (1 1 0) surface of Ru-doped TiO 2 , Ti-doped RuO 2 and the industrially important Dimensionally Stable Anode (DSA) composition Ru 0.3 Ti 0.7 O 2 have been examined using density functional theory. It is found that the oxygen adsorption energy on a Ti site is strongly aected by the presence of small amounts of Ru dopant, whereas oxygen adsorption is relatively unaected by Ti dopants in RuO 2. The calculations also indicate that coordinatively unsaturated Ti sites on Ru-dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 40 publications
(50 reference statements)
2
51
0
Order By: Relevance
“…Ru based catalysts have shown selectivity for both OER and ClER. While most of the Ru based studies had a focus on the ClER35,[50][51][52][53] or the fundamental understanding of the ClER on ruthenium titanium oxide (RTO)46,[54][55][56] , there are a few studies that reported enhanced selectivity towards OER on someRu-based catalysts. Some speculated that doping of Zn into RuO2 crystal structure caused a rearrangement of the local atomic structure in the vicinity of the Zn ions, enhancing the oxygen evolution process at positive potentials and, overall, improving the selectivity of the OER in chloride containing acidic media 57 .…”
mentioning
confidence: 99%
“…Ru based catalysts have shown selectivity for both OER and ClER. While most of the Ru based studies had a focus on the ClER35,[50][51][52][53] or the fundamental understanding of the ClER on ruthenium titanium oxide (RTO)46,[54][55][56] , there are a few studies that reported enhanced selectivity towards OER on someRu-based catalysts. Some speculated that doping of Zn into RuO2 crystal structure caused a rearrangement of the local atomic structure in the vicinity of the Zn ions, enhancing the oxygen evolution process at positive potentials and, overall, improving the selectivity of the OER in chloride containing acidic media 57 .…”
mentioning
confidence: 99%
“…OER selectivity issue. Hitherto, this selectivity problem was studied by Δ E O as descriptor in junction with conventional volcano analyses . This finding motivates to re‐investigate the CER vs .…”
Section: Discussionmentioning
confidence: 99%
“…Hitherto, this selectivity problem was studied by ΔE O as descriptor in junction with conventional volcano analyses. [28][29][30][31] This finding motivates to re-investigate the CER vs. OER selectivity, applying ΔG OÀ OH as descriptor, with advanced material-screening frameworks, such as overpotential-dependent volcano plots, kinetic scaling relations, or activity maps based on the electrochemical-step symmetry index; [45][46][47]70,71,80] these concepts have been recently introduced by the author and have shown to provide better results in thorough sorting of electrode materials compared to the conventionally applied volcano scheme. [48,74] Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations